Features of Diagnosing and Managing a Patient with DiGeorge Syndrome - O.S. Koreniuk; T.V. Yaroshevska; I.H. Samoilenko; T.V. Baralei (Zaslavsky O.Yu., 2016)
The article presents a case of own clinical observation of DiGeorge syndrome (22q11.2 chromosome deletion syndrome) in a child. The features of the disease course with the dominance of clinical symptoms of congenital malformations of the heart, blood vessels and lungs are noted. This case demonstrates the difficulty of diagnosing incomplete DiGeorge syndrome with moderate immunological disorders and transient hypocalcemia. Patient management should be focused not only on the surgical correction of congenital heart disease, but also on the prevention of recurrent infections and hypocalcemia, which prevents the complicated course of the disease and determines a favorable prognosis.